(untitled) (Tempo e Argumento, 2009)
Augusto da Silva, Universidade Federal de Sergipe Dorval do Nascimento, Universidade do Extremo Sul Catarinense Enrique Serra Padrós, Universidade Federal do Rio Grande do Sul Ivonete Pereira, Universidade Estadual do Oeste do Paraná Lucília de Almeida Neves Delgado, Universidade de São Paulo Paulo Rogério Melo de Oliveira, Universidade do Sul de Santa Catarina Raimundo Pereira Alencar Arrais, Universidade Federal do Rio Grande do Norte Reinaldo Lindolfo Lohn, Universidade do Estado de Santa Catarina Silvia Maria Fávero Arend, Universidade do Estado de Santa Catarina Zita Rosane Possamai, Universidade Federal do Rio Grande do Sul